Does Trade Protection Improve Firm Productivity? Evidence from Philippine Micro Data - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2010)
The recent trade and productivity literature shows that trade liberalization can lead to productivity gains through increased competition and exit of inefficient firms and reallocation of market shares in favor of more efficient firms. In this paper, an attempt is made to examine the impact of trade liberalization on firm productivity in the Philippines. The country presents an interesting case due to its adoption of selective protection amidst an incomplete trade liberalization process. Based on an unbalanced firm-level panel dataset covering an eight-year period from 1996 to 2006, the results provide some evidence in support of the hypothesis that trade liberalization leads to productivity gains and conversely, protection leads to productivity losses. This is confirmed by the negative and significant coefficient on EPR for the purely importable sector. The results tend to indicate that the selective protection policy undermined the process of output restructuring and reshuffling of resources from less productive to more productive firms as protection of selected industries allowed the survival of inefficient firms.
Keywords: 330; trade liberalization; total factor productivity; Philippines; selective protection; Philippine manufacturing industry; Handelsliberalisierung; Protektionismus; Produktivität; Industrie; Philippinen